Dendrimer-Entrapped Gold Nanoparticles as Potential CT Contrast Agents for Localizing Sentinel Lymph Node via Indirect CT Lymphography on Rabbit Model. (17th April 2018) - Shi, Fang; Yang, Yue; Chen, Jian; Sha, Yan; Shu, Yilai; Wu, Haitao
Abstract : Objective . To investigate the potential use of indirect computed tomography lymphography (CT-LG) with dendrimer-entrapped gold nanoparticles (Au DENPs) in the localization and enhanced imaging of cervical sentinel lymph node (SLN) on rabbit model. Methods . Twelve rabbits were randomly divided into two groups: the positive control group and the experimental group. In the control group, indirect CT-LG was performed with the injection of 0.5 ml activated carbon nanoparticles (ACNP) and Omnipaque mixture suspension in the right tongue submucosa. CT images were acquired before the injection and 1, 5, 10, and 15 min after the injection, respectively. In the experimental group, indirect CT-LG injection with 0.5 ml Au DENPs suspension was performed in the right tongue submucosa. CT images were obtained before the injection and 1, 5, 10, and 15 min and 1, 2, 6, 24, 48, and 72 h after the injection, respectively. Then, SLN identification and enhancement characteristics were evaluated. Results . Indirect CT-LG revealed the enhancement of one right deep cervical lymph nodes in all animals, which was SLN. SLN location was marked with black color (ACNP dye) or purple-black color (Au DENPs dye). At each detection time point, the enhanced SLN attenuation values of control rabbits were statistically significantly higher than that of the plain scan, respectively (P < 0.05 ). Also the values of experimental rabbits were statistically significantly higher than that of the control at the same time point after injection (P < 0.05 ). The detection rate of SLN was 100%. Conclusions . Indirect CT-LG with injection of Au DENPs as CT contrast agents can locate the SLN for a long period of time and enrich the SLN black dye. It is helpful for SLNs identification during the operation.